Barriers to Voluntary Medical Male Circumcision Uptake to Prevent HIV Transmission: A Qualitative Study among Married Men - Josephine, Aryek-kwe; Grace, Nambozi; Kabunga, Amir (International Journal of Academic Research in Business and Social Sciences, 2023)
Background: Voluntary medical male circumcision (VMMC) is a relatively new intervention that has been found to reduce sexual transmission of HIV among heterosexual partners by 60% when properly practiced. However, the poor acceptance of VMMC makes it difficult to accomplish the objectives of health policy to boost uptake. The purpose of this study was to explore the barriers to VMMC Uptake among married men in Kitgum municipality. Methods: The qualitative descriptive design was employed in this study. The purposive sampling method was used to recruit 30 married men who lived within any of the three divisions of the municipality and had been married for at least one year. Data collection was done using an in-depth interview method. Inductive content analysis was used to generate the themes and categories. Results: The study findings revealed that fear, financial uncertainty, involvement of female health workers, cultural beliefs, religious belief, sexual dissatisfaction and advanced age were barriers to voluntary medical male circumcision uptake among the married men in Kitgum municipality. Conclusion: In Kitgum municipality, VMMC Uptake is still low, but the majority of the males had sufficient knowledge about it. We found the low uptake was primarily attributed to anxiety, involvement of female health workers, financial instability, sexual unhappiness, and advanced age. There is a need for proper re-packaging of the health education messages during mobilisations to address the anticipated side effects and to clearly state the reasons for the VMMC program. There is a need for proper re-packaging of the health education messages during mobilisations to address the communication gaps and to clearly state the reasons for VMMC program. Adequate psychological preparation of the men to expect any sex of staffs working in these clinics.
Keywords: HIV Transmission; Medical Male Circumcision; HIV Transmission; Sexual Performance; Cultural Beliefs; HIV Prevention